2017
DOI: 10.1002/jcsm.12232
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial degeneration precedes the development of muscle atrophy in progression of cancer cachexia in tumour‐bearing mice

Abstract: BackgroundCancer cachexia is largely irreversible, at least via nutritional means, and responsible for 20–40% of cancer‐related deaths. Therefore, preventive measures are of primary importance; however, little is known about muscle perturbations prior to onset of cachexia. Cancer cachexia is associated with mitochondrial degeneration; yet, it remains to be determined if mitochondrial degeneration precedes muscle wasting in cancer cachexia. Therefore, our purpose was to determine if mitochondrial degeneration p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
331
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 212 publications
(381 citation statements)
references
References 67 publications
28
331
5
Order By: Relevance
“…Oxidative stress, the imbalance between pro‐oxidant generation and antioxidant defence, has been implicated in pathological conditions of skeletal muscle, including sarcopenia, denervation, and cancer cachexia . Excess levels of reactive oxygen species (ROS) impair contractile function of skeletal muscle and activate proteases that are associated with degradation of contractile machinery .…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress, the imbalance between pro‐oxidant generation and antioxidant defence, has been implicated in pathological conditions of skeletal muscle, including sarcopenia, denervation, and cancer cachexia . Excess levels of reactive oxygen species (ROS) impair contractile function of skeletal muscle and activate proteases that are associated with degradation of contractile machinery .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, we now report cancer and chemotherapy acting synergistically, impairing mitochondrial homeostasis from the biogenesis and degradation, to the dynamic processes that modify the mitochondrial network and, in turn, its efficiency (47). Consistently, tumor‐bearing mice exhibited, even if not necessarily simultaneously, reduced levels of PGC‐lα and mitochondrial number, increased mitophagy, and altered mitochondrial dynamics (9, 10, 12). These impairments could lead to altered mitochondrial morphology, reducing oxidative capacity and energy stores (9).…”
Section: Discussionmentioning
confidence: 79%
“…In addition, decreased muscle succinate dehydrogenase (SDH) activity and oxidative fiber proportion were observed in tumor hosts, further supporting the idea that mitochondria could play a central role in cancer‐induced muscle atrophy (9, 11). The observation that mitochondrial alterations precede muscle loss in mice bearing the Lewis lung carcinoma (12) suggests that targeting muscle energetics may prevent or at least delay the onset of muscle wasting.…”
mentioning
confidence: 99%
“…Gross observation of mice under aspiration challenge showed that mice became lean with decreased physical activity. These characteristics might be similar to the muscle atrophy induced by cancer and glucocorticoids . Reduced body weight by the aspiration challenge may reflect the lean appearance of mice .…”
Section: Discussionmentioning
confidence: 83%